Pengembangan Penuntun Praktikum Materi Adsorpsi Isoterm Berbasis Tumbuhan Indigofera tinctoria L dengan Pendekatan Inkuiri Terbimbing - Rikah Indriyani; Erlina Erlina; Ira Lestari; Hairida Hairida; Rody Putra Sartika; Husna Amalya Melati*; Risya Sasri (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
The available guides in chemical kinetic’s learning only explain the adsorption equation, do not explain the type of adsorption and the practical guide is not related to the value of local wisdom. Therefore, it is necessary to have a practical guide on the concept of adsorption isotherm based on local wisdom. The purpose of this study was to determine the feasibility of the laboratory work’s guide and student responses. This research employs a research and development (R D) using ADDIE’s model. The subject in this study was a lab work’s guide for the plant-based isotherm adsorption topic Indigofera tinctoria L utilizing a guided inquiry approach which was tested to 13 students in a limited scale and 34 students in the main scale. The experiment was conducted to chemistry education students of FKIP Untan on academic year 2018-2020 who had learned chemical kinetics courses. Data collection techniques used are direct and indirect communication techniques. Data collection tools used are the feasibility assessment sheets and student response questionnaire. The results of the feasibility assessment in terms of content, graphic and language aspects obtained an average of 91% with very feasible criteria. The results of the limited trial obtained an average of 89% and the results of the main trial of 89% each obtained very good criteria. Based on the results of the feasibility assessment by experts and student responses’ questionnaire that the lab work’s guide can be used in learning process to support students’ understanding of chemical kinetics’ concepts